Plastic and Microplastic in the Environment: Management and Health Risks - Ahamad A.; Singh P.; Tiwary D. (My University, 2025)
In Plastic and Microplastic in the Environment: Management and Health Risks, a team of distinguished environmental researchers delivers an up-to-date exploration of plastic and microplastic environmental contamination, conventional and advanced plastics management techniques, and the policies adopted across the globe to combat the phenomenon of plastics contamination. Containing a balanced focus on both conventional plastics and microplastics, this book discusses the potential health issues related to plastic and microplastic infiltration in a variety of global environments and environmental media, including freshwater environments, oceanic environments, soil and sediment, and air. Insightful treatments of commercial and social issues, including the roles of corporate social responsibility initiatives and general education in the fight against plastic and microplastic pollution, are provided as well. Plastic and Microplastic in the Environment also includes: A thorough introduction to plastic debris in global environments, including its accumulation and disintegration Comprehensive explorations of policies for strengthening recyclable markets around the world Practical discussions of the prevalence of microplastics in the marine environment, air, soil, and other environmental media In-depth examinations of wastewater treatment plants as a potential source point of microplastics, as well as conventional and advanced microplastic particle removal technologies Perfect for academics, postgraduates and advanced undergraduates in fields related to environmental science and plastics, Plastic and Microplastic in the Environment: Management and Health Risks will also earn a place in the libraries of professionals working in the plastics industries and environmental policymakers. © 2022 John Wiley & Sons Ltd. All rights reserved.